Reconnaissance of Karstic Dolines in the Area Between Benina-Al-Abyar, NE Libya. - Mohamed S. Al Faitouri; Ahmed M. Muftah; Kalifah A. Ashahomi; Saad K. Elebaidi; Hwaidi A. Errishi; Hwaidi A. Errishi; Osama A. El Fallah (Libyan Journal of Science &Technology, 2026)
Karst features are widespread, yet many remain insufficiently documented despite their scientific and environmental importance. The present study focuses on the area between Al-Abyar and Benina villages in Cyrenaica, where large-scale dolines have developed within the Upper Miocene Wadi Al Qattarah Formation. Field surveys and morphometric analyses revealed sixteen representative dolines distributed across two geomorphic levels: the coastal fluvial plain and the first plateau of Al Jabal al Akhdar. These dolines vary in size, morphology, and genesis, ranging from solutional depressions to collapse and alluvial dolines. Their formation is interpreted in relation to tectonic evolution, groundwater circulation, surface runoff dynamics, and lithological variability. The study highlights how structural discontinuities and lithological heterogeneity have controlled doline development, while human activities such as agriculture, groundwater extraction, and infrastructure expansion have contributed to their enlargement and reactivation. This anthropogenic influence increases the hazard potential of dolines, posing risks to land use and settlement stability. By integrating petrographic analysis, GIS mapping, and morphometric characterization, the research provides new insights into karst evolution in Cyrenaica and establishes a baseline for future comparative studies with other doline fields in Al Jabal al Akhdar. Ultimately, the findings emphasize the need for conservation strategies to protect these natural karst systems, not only for their geomorphological and hydrogeological significance but also for their potential value in geotourism and sustainable regional development.